Solar Cells New Approaches and Reviews - Kosyachenko, Leonid A. (IntechOpen, 2015)
This book contains chapters in which the problems of modern photovoltaics are considered. The majority of the chapters provide an overview of the results of research and development of different types of solar cells. Such chapters are completed by a justification for a new solar cell structure and technology. Of course, highly effective solar energy conversion is impossible without an in-depth examination of the solar cell components as physical materials. The relations between structural, thermodynamic, and optical properties of the physical material without addressing the band theory of solids are of both theoretical and practical interest. Requirements formulated for the material are also to be used for maximally efficient conversion of solar radiation into useful work.